Genetic polymorphisms and cerebrovascular disease in children with sickle cell anemia from Rio de Janeiro, Brazil - Isaac Lima da Silva Filho; Ana Claudia Celestino Bezerra Leite; Patrícia Gomes Moura; Georgina Severo Ribeiro; Andréa Cony Cavalcante; Flávia Carolina Marques de Azevedo; Maria José de Andrada-Serpa (Arquivos de Neuro-Psiquiatria)
The aim of the present work was to examine possible genetic risk factors related to the occurrence of cerebrovascular disease (CVD) in Brazilian population, the frequency of βS-globin gene haplotypes and co-inheritance with α-thalassemia (-α3.7kb) and single nucleotide polymorphism of methylenetetrahydrofolate reductase (MTHFR-C677T), Factor V Leiden (FV-G1691A) and prothrombin (PT-G20210A) genes in children from Rio de Janeiro. Ninety four children with sickle cell anemia (SCA) were included, 24 patients with cerebrovascular involvement and 70 patients without CVD as control group. The mean age of children at the time of the cerebrovascular event was similar to the control group. The frequency of -α3.7kb thalassemia was similar in both groups (p=0.751). Children with Bantu/Atypical βS-globin gene haplotype presented 15 times more chance (OR=15.4 CI 95% 2.9-81.6) of CVD than the other βS-globin gene haplotypes. The C677T polymorphism of MTHFR gene was similar in both groups (p=0.085). No mutation in the FV Leiden or PT genes was found. A large study seems necessary to establish the role of these genetic polymorphisms in Brazilian miscegenated population.